Comprehending cinema - MacDonald, Scott 1942- (Oxford University Press, 2024)
"Comprehending cinema is a collection of in-depth interviews and panoramic essays that models a generalist approach to modern audiovisual media, prioritizing remarkable cinematic accomplishments that can get lost within our overwhelming modern mediascape. The 18 interviewees featured in this publication include Oscar-winning documentarians Daniel Lindsay and T.J. Martin; Dean Fleischer Camp, whose Marcel the Shell with Shoes On was an internet smash, then an Oscar nominee; canonical filmmakers Guy Maddin and Su Friedrich. still building on remarkable careers; renowned poet (and cineaste) John Ashbery; Irish independent Tadhg O'Sullivan who is entranced by the moon; indefatigable cine-historian, Paul Cronin; LA artist Jennifer West, who collaborated with 11,500 visitors on New York City's High Line to produce a new kind of City Symphony; Penny Lane, whose documentary films continually surprise; a collaborative filmmaking team who provide an immersive motion study of a crowd taking selfies with the Mona Lisa; cine-explorers Lucien Castaing-Taylor and Véréna Paravel; master of the cine-archive Bill Morrison; cine-scientist Erin Espelie; video-essayist Chloé Galibert-Lainé; and the Alloy Orchestra who entertained silent-film audiences for three decades. Comprehending Cinema combines engaging conversations with accomplished filmmakers and essayistic explorations of recent contributions to modern media-making by Ukranian filmmaker Sergei Loznitsa, by filmmakers creating a tradition of "cine-nocturnes," and by filmmakers exploring archival representations of World War 1. The book offers a reading adventure dedicated to opening the door to exciting new kinds of film experience." --
Keywords: Geschichte; Film; Motion pictures / History; Experimental films / History and criticism; Cinéma / Histoire; Interview; Aufsatzsammlung